Prevalence of immediate hypersensitivity reactions to cow's milk in infants based on skin prick test and questionnaire - (:unkn) unknown (ELSEVIER DOYMA SL, 2008)
Objective: Cow's milk (CM) hypersensitivity is one of the most frequent hypersensitivities in infants. The objective of our study was to investigate the prevalence of immediate hypersensitivity to CM based on skin prick test results and to evaluate associated allergic conditions ascertained by questionnaire in infants living in Istanbul. Methods: All infants born between June 2001 and May 2002 were recalled to the hospital according to their dates of birth, and 1015 infants aged between 8-18 months were included in the study. An interview was conducted with each mother and a questionnaire requesting data on cow's milk hypersensitivity and other allergic diseases was completed during this interview. A cow's milk skin prick test (SPT) was applied to all infants. An open CM challenge test was then carried out on infants with a positive SPT to CM. Results: Among the 1015 infants who underwent SPT six (0.59 %) demonstrated immediate hypersensitivity to the CM allergen and three (0.29 %) developed a positive response to the CM challenge test. The results of the questionnaire revealed that 112 (11.0 %) of the infants had family history of allergic diseases, 96 infants (9.5 %) had a positive history of recurrent wheezing, and 166 (16.4 %) had a history of skin rash resembling atopic dermatitis. Conclusions: Our results suggest that CM hypersensitivity, with its low prevalence, might not be a serious health concern in Turkish infants.
Keywords: Immediate hypersensitivity; Cow's milk allergy; Skin prick test; Allergic diseases; Infant; 1ST 3 YEARS; ALLERGEN AVOIDANCE; ADVERSE-REACTIONS; CONTROLLED-TRIAL; CLINICAL-COURSE; ATOPIC DISEASE; YOUNG-CHILDREN; FOLLOW-UP; PREVENTION; MANAGEMENT